(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Trichoderma harzianum, a well-known biocontrol agent, has shown remarkable potential in controlling various plant pathogenic fungi. However, the efficacy of Trichoderma-based biofungicides can be influenced by the presence of chemical fungicides in the environment. The present study aimed to assess the compatibility of Trichoderma harzianum with the widely used synthetic fungicide, captan using the Poisoned Food Technique. The Poisoned Food Technique is a reliable method for investigating the potential antagonistic effects between biocontrol agents and chemical fungicides. In this study, varying concentrations of 60% captan fungicide were incorporated into a growth medium used for cultivating Trichoderma harzianum. The bioassays were conducted in a controlled laboratory setting. The results revealed that the compatibility of Trichoderma harzianum with 60%% captan fungicide was maximum at 800 ppm followed by 400 ppm, 600 ppm and 1000 ppm. Least compatibility was seen at 200 ppm. In conclusion, this study provides valuable insights into the compatibility of Trichoderma harzianum with 60% captan fungicide. The findings highlight the importance of understanding the interaction between biocontrol agents and chemical fungicides to maximize disease management efficiency while minimizing any potential negative impacts on beneficial microorganisms. These results contribute to the development of sustainable and effective agricultural practices that harness the synergistic potential of both biocontrol agents and chemical fungicides.